Using real-world data to inform dosing strategies of rituximab for pediatric patients with frequent-relapsing or steroid-dependent nephrotic syndrome: a prospective pharmacokinetic-pharmacodynamic study - Chen, Yewei; Shen, Qian; Xiong, Ye; Dong, Min; Xu, Hong; Li, Zhiping (Frontiers in Pharmacology, 2024)
Objectives: Rituximab is frequently used off-label for the treatment of frequentrelapsing/steroid-dependent nephrotic syndrome (FRNS/SDNS). However, the optimal dosing schedules remain undetermined. The objective of this study was to establish a population pharmacokinetic-pharmacodynamic (PK-PD) model in pediatric patients with FRNS/SDNS, and to investigate dosing regimens that provide adequate suppression of B lymphocytes.A prospective, open-label, single-center study was conducted in Nephrology Department at Children's Hospital of Fudan University, and a two-compartment PK model of rituximab in pediatric FRNS/SDNS has been developed previously by our group. CD19+ lymphocyte count profiles were obtained from these patients. The presence of anti-rituximab antibodies was assessed prior to medication in children who had previously received rituximab or during follow-up at the last sampling point for PK analysis. PK-PD analyses were performed to describe the changes of CD19+ lymphocytes, with rituximab assumed to increase their death rate. Monte Carlo 3 simulation was conducted to evaluate different dosing regimens.In total, 102 measurements of CD19+ lymphocyte counts were available for PK-PD analysis. No detectable levels of anti-rituximab antibodies were observed during the PK follow-up period. A turnover model with saturable stimulatory action of rituximab on the removal of lymphocytes best characterized the relationship between rituximab concentration and CD19+ lymphocyte counts, where the Emax and EC50 were estimated to be 99.6*10 6 /L and 5.87 µg/ml, respectively. Simulations indicated that a single infusion of 750 mg/m 2 and 2 infusions of 375 mg/m 2 both yielded a 10-week suppression of CD19+ lymphocytes.This study represents a first attempt to quantitatively describe the PK-PD relationship of rituximab in pediatric patients with FRNS/SDNS, and provide a potential pathway for future precision dosing strategy for rituximab therapy. Further clinical studies are warranted to evaluate the efficacy and safety of different dosing schemes.